Factors Associated with Health-Seeking Preference Among People Who Were Supposed to Cough for More Than 2 Weeks: A Cross-Sectional Study in Southeast China - Wang W; Wang F; Peng Y; Liu K; Chen X; Chai C; Wang X; Chen B (Patient Preference and Adherence, 2020)
Wei Wang,1 Fei Wang,1 Ying Peng,1 Kui Liu,1 Xinyi Chen,2 Chengliang Chai,1 Xiaomeng Wang,1 Bin Chen1,3 1Department of Tuberculosis Control and Prevention, Zhejiang Provincial Center for Disease Control and Prevention, Hangzhou 310051, People’s Republic of China; 2Department of Preventive Medicine, Epidemiology and Health Statistics, School of Medicine, Ningbo University, Ningbo 315211, People’s Republic of China; 3Key Laboratory of Vaccine, Prevention and Control of Infectious Disease of Zhejiang Province, Zhejiang Provincial Center for Disease Control and Prevention, Hangzhou 310051, People’s Republic of ChinaCorrespondence: Bin Chen; Xiaomeng WangDepartment of Tuberculosis Control and Prevention, Zhejiang Provincial Center for Disease Control and Prevention, 3399, Binsheng Road, Binjiang District, Hangzhzou, Zhejiang Province 310051, People’s Republic of ChinaTel/Fax +86 571 8711 5183; Tel +86 571 8711 5181Fax +86 571 8711 5189Email bchen@cdc.zj.cn; xmwang@cdc.zj.cnBackground: The health-seeking preference of people with a cough > 2 weeks had not been extensively researched in southeast China. The study aimed to explore factors associated with health-seeking preference, which could provide more evidence to improve individuals’ appropriate health-seeking behavior.Materials and Methods: From October 2018 to December 2018, this cross-sectional study was conducted in Zhejiang, China. A questionnaire was used to collect information on sociodemographic characteristics, knowledge of tuberculosis (TB), and health-seeking preference. The chi-square test and multivariable logistic regression were performed to evaluate factors associated with health-seeking preference.Results: Of the 7174 participants, 3321 (46.3%) were men, 6148 (85.7%) were married, and 6013 (83.8%) knew about TB. Appropriate health-seeking preference was reported by 6229 (86.8%) participants. Respondents knowing about TB were more likely to seek appropriate care than those did not (89.6% vs 72.4%, p< 0.001). Of the 6013 participants knowing about TB, respondents with higher scores on five key items of TB knowledge were more likely to get appropriate health-seeking preference. About 805 (96.6%) participants with 5 scores on TB knowledge had appropriate care preference. Only 97 (72.4%) participants with a score of 0 reported an appropriate preference. Multivariable logistic regression showed residence, marital status, education level, occupation, and awareness of TB knowledge were predictors of appropriate health-seeking preference. Compared to participants with a score of 0 on five TB key knowledge, participants with a score of 5 were 8.57 times more likely to have appropriate health-seeking preference (95% confidence interval [CI]: 4.97– 14.78), followed by a score of 4 (odds ratio [OR]=5.99, 95% CI, 3.23– 8.03); 3 (OR=3.74, 95% CI, 2.44– 5.74); 2 (OR=1.99, 95% CI, 1.30– 3.02) and 1 (OR=1.17, 95% CI, 0.76– 1.80).Conclusion: Participants with little knowledge of TB had a low level of appropriate health-seeking preference. Appropriate health-seeking preference of the participants improved with increased key knowledge level of TB.Keywords: tuberculosis, health care-seeking behavior, cough